Levels, Trends, and Factors Associated with Under-5 Excess Mortality among Twins in Sub-Saharan Africa: Studies of National Surveys from 42 Countries - (:unkn) unknown (My University, 2021)
Twin children are more likely to die than singletons. In sub-Saharan African countries, this is an additional burden, as child mortality levels are already higher than anywhere else.This article presents under-5 mortality rates (U5MR) for twins and singletons in sub-Saharan Africa from 1986 to 2016. It describes the geographical variations and changes over time. It also describes the variation of twins’ excess mortality according to age, between 0 and 5 years old. Moreover, it analyses the factors associated with twins’ excess mortality. We used data from 156 national surveys (Demographic and Health Surveys (DHS) & Multiple Indicator Cluster Survey) from 42 countries. The findings show that U5MR are, on average, 3 times higher among twins compared to singletons. The multivariate results show that, all else being equal, the adjusted Hazard Ratio (HRa) of twins is 3.2 times higher (2.9 -3.3; p<0.001) than that of singletons. The main factors associated with excess mortality risks among twins are a set of biomedical and nutritional features, composed of birthweight, caesarean section, antenatal visits and breastfeeding. Among these factors, non-breastfeeding is associated with 4 times higher mortality risks for twins than for singletons; and caesarean delivery is associated with lower mortality risks for twins than for singletons.
Keywords: African Research